Evoked Potentials and Memory/Cognition Tests Validate Brain Atrophy as Measured by 3T MRI (NeuroQuant) in Cognitively Impaired Patients - Braverman, Eric R. (PLoS One, 2015)
To our knowledge, this is the largest study evaluating relationships between 3T Magnetic Resonance Imaging (MRI) and P300 and memory/cognitive tests in the literature. The 3T MRI using NeuroQuant has an increased resolution 15 times that of 1.5T MRI. Utilizing NeuroQuant 3T MRI as a diagnostic tool in primary care, subjects (N=169; 19–90 years) displayed increased areas of anatomical atrophy: 34.62% hippocampal atrophy (N=54), 57.14% central atrophy (N=88), and 44.52% temporal atrophy (N=69). A majority of these patients exhibited overlap in measured areas of atrophy and were cognitively impaired. These results positively correlated with decreased P300 values and WMS-III (WMS-III) scores differentially across various brain loci. Delayed latency (p=0.0740) was marginally associated with temporal atrophy; reduced fractional anisotropy (FA) in frontal lobes correlated with aging, delayed P300 latency, and decreased visual and working memory (p=0.0115). Aging and delayed P300 latency correlated with lower FA. The correlation between working memory and reduced FA in frontal lobes is marginally significant (p=0.0787). In the centrum semiovale (CS), reduced FA correlated with visual memory (p=0.0622). Lower demyelination correlated with higher P300 amplitude (p=0.0002). Compared to males, females have higher demyelination (p=0.0064). Along these lines, the higher the P300 amplitude, the lower the bilateral atrophy (p=0.0165). Hippocampal atrophy correlated with increased auditory memory and gender, especially in males (p=0.0087). In considering temporal lobe atrophy correlations: delayed P300 latency and high temporal atrophy (p=0.0740); high auditory memory and low temporal atrophy (p=0.0417); and high working memory and low temporal atrophy (p=0.0166). Central atrophy correlated with aging and immediate memory (p=0.0294): the higher the immediate memory, the lower the central atrophy. Generally, the validation of brain atrophy by P300 and WMS-III could lead to cost-effective methods utilizable in primary care medicine following further confirmation.